Brevibacterium rongguiense sp. nov., isolated from freshwater sediment. Issue 10 (20th October 2020) - Deng, Tongchu; Lu, Huibin; Qian, Youfen; Chen, Xingjuan; Yang, Xunan; Guo, Jun; Sun, Guoping; Xu, Meiying
Abstract : A Gram stain-positive, non-spore-forming, non-motile and rod-shaped actinomycete, strain 5221 T, was isolated from the sediment of a river collected at Ronggui in the Pearl River Delta, PR China. Phylogenetic analysis based on 16S rRNA gene sequences revealed that the strain formed a distinct lineage within the genus Brevibacterium and had the highest sequence similarity to Brevibacterium pityocampae Tp12 T (96.7 %), followed by Brevibacterium daeguense 2C6-41 T (96.5 %), Brevibacterium samyangense SST-8 T (96.0 %) and Brevibacterium ravenspurgense 20 T (95.9 %). The results of chemotaxonomic analyses, including detecting anteiso-C15 : 0, anteiso-C17 : 0, and C16 : 0 as the major cellular fatty acids, diphosphatidylglycerol, phosphatidylglycerol and three phosphoglycolipids as the polar lipids, MK-8(H2 ) as the major menaquinone, and a DNA G+C content of 72.4 mol%, supported that strain 5221 T is a member of the genus Brevibacterium . Furthermore, low sequence similarities of 16S rRNA gene sequences, differences in fatty acid compositions and differential physiological characteristics such as enzyme activity and carbon sources utilization ability distinguished the isolate from its close relatives. Therefore, strain 5221 T represents a novel species of the genus Brevibacterium, for which the name Brevibacterium rongguiense sp. nov. is proposed, with the type strain 5221 T (=GDMCC 1.1766 T =KACC 21700 T ).